2020
DOI: 10.2196/14351
|View full text |Cite
|
Sign up to set email alerts
|

Needs, Experiences, and Views of People With Rheumatic and Musculoskeletal Diseases on Self-Management Mobile Health Apps: Mixed Methods Study

Abstract: Background Despite the growing interest and exponential popularity of mobile health (mHealth) apps for long-term conditions such as rheumatic and musculoskeletal diseases (RMDs) and their self-management, patients are rarely directly consulted and involved in the app development process. Objective This study aims to explore the needs, experiences, and views of people diagnosed with RMDs on mHealth apps. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 35 publications
6
30
0
4
Order By: Relevance
“…For example, they have been useful tools to facilitate the calculation of disease activity scores, and monitor patients through the collection of clinical and laboratory parameters 10. A survey performed among people living with RMDs (429 respondents) revealed that around 50% were aware of the existence of such apps 11. This corresponds with previous works performed in different specialties.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…For example, they have been useful tools to facilitate the calculation of disease activity scores, and monitor patients through the collection of clinical and laboratory parameters 10. A survey performed among people living with RMDs (429 respondents) revealed that around 50% were aware of the existence of such apps 11. This corresponds with previous works performed in different specialties.…”
Section: Introductionsupporting
confidence: 80%
“…Financial affordability was discussed during the TF meeting. In our survey, the majority of people living with RMDs did not wish to pay for the apps 11. It was agreed by the TF that cost should be limited as much as possible, to remain affordable.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…To our knowledge, this is the first work depicting a German mHealth patient perspective in rheumatology. This work may inform mHealth policy recommendations and adds to the growing body of eHealth rheumatology knowledge [ 11 - 14 , 24 , 25 ] by providing detailed patient preferences, needs, and barriers. Hence, we believe that the results of this study could help in devising mHealth solutions that can be integrated into the clinical routine of patients with rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients demanded clear recommendations from the national society for rheumatology and expressed the highest confidence in an app developed by a rheumatic disease scientific society [ 25 ]. Our results suggest that patient app entries should take no longer than 15 minutes and should not be requested more often than weekly.…”
Section: Discussionmentioning
confidence: 99%